House-warming: Wild king cobra nests have thermal regimes that positively affect hatching success and hatchling size. (February 2023) - Dolia, Jignasu; Das, Abhijit; Kelkar, Nachiket
Abstract: Incubation temperature in nests of oviparous reptiles affects reproductive success indicators, including hatching time and success, offspring size, fitness, and behaviour. The female king cobra builds an above ground nest to incubate and protect its eggs. However, it is not clear how thermal regimes inside king cobra nests respond to external environmental temperature regimes, especially in subtropical regions that witness high diel and seasonal temperature fluctuations. To better understand the relationship between inside nest temperatures and hatching outcomes for this snake, we monitored the thermal regimes of 25 natural king cobra nests in the subtropical forests of the Western Himalayas in Uttarakhand state, northern India. We hypothesized that inside nest temperatures would be higher than outside (ambient) temperatures and that thermal regimes inside nests would affect hatching success and hatchling size. Internal and external temperatures at nest sites were measured every hour until hatching, via automatic data loggers. We then calculated hatching success of eggs and measured hatchling length and weight. Mean inside nest temperatures were consistently higher by about 3.0 °C than outside environmental temperatures. External temperature reduced with increasing elevation of nest sites and was the best determinant of inside nest temperature, which had a smaller range of variability. Physical characteristics of nests (size and leaf materials used) did not influence nest temperature significantly, but nest size was positively related to clutch size. Mean inside nest temperature was the best predictor of hatching success. Average daily minimum nest temperature, which indicates a possible lower threshold for thermal tolerance by eggs, was also correlated positively with hatching success. Mean daily maximum temperature was a significant predictor of mean length of hatchlings, but not of mean hatchling weight. Our study provides unequivocal evidence for the critical thermal benefits of king cobra nests for increased reproductive success, in subtropical environments with lower and sharply fluctuating temperature regimes. Highlights: First study on temperature regimes of 25 king cobra nests from a subtropical habitat. Nest temperatures, warmer than ambient temperatures, were maintained across most nests. Mean nest temperature positively affected king cobra hatching success and hatchling length. Temperature effects were consistent, irrespective of nest material, elevation, and location. High relevance of findings for studies on thermal adaptation in reptiles in cold climates.